Impact of the COVID-19 pandemic on psychotropic medication uptake in Northern Ireland: a population-wide trend analysis. (November 2021) - Kent, Lisa; O'Reilly, Dermot; Maguire, Aideen
Abstract: Background: The COVID-19 pandemic and associated lockdowns were predicted to have a major impact on mental health; however, studies on this issue present contradictory findings. Mental ill-health indicators have exhibited strong upward trends over the past decade, but recent studies exploring psychotropic medication uptake have relied on simple counts in the year before and after lockdown, which can give a false impression of the scale of the pandemic's effect. This study uses 9 years of linked, individual-level, administrative data to identify changes in psychotropic medication uptake before and after the pandemic. Methods: Psychotropic and antiepileptic (counterfactual comparator) medication data were extracted from the population-wide Enhanced Prescribing Database (EPD), which captures all medications dispensed in community pharmacies across Northern Ireland. Prescriptions remain free in Northern Ireland; therefore, EPD captures more than 99% of medications dispensed, but monthly scan rates can be lower. Individual-level demographic and socioeconomic indicators were obtained from general practitioner registration data for everyone aged older than 10 years (approximately 1·5 million). Denominators varied monthly, including all individuals alive and resident that month. Monthly prescription counts were split (prelockdown Jan 1, 2012 to Feb 29, 2020; post lockdown March 1 to Oct 31, 2020). Auto Regressive Integrated Moving Average models were trained in R, version 4.1.0, taking into consideration trends and seasonal effects. The forecast (expected) monthly values were compared to actual monthly values, stratified by demographic factors. Findings: Over the study period, approximately 31·4% (n=566 594) of the study population had received antidepressant, 13·6% (n=244 515) hypnotic, 3·6% (n=65 565) antipsychotic, 17·4% (n=312 849) anxiolytic, and 9·3% (n=167 518) antiepileptic medications at some point, with strong upward trends for all medications 2012–20. In March, 2020, when restrictions began, all medication uptake increased beyond the CIs of the expected value, followed by a decrease April–May, 2020, mostly returning to the expected trend thereafter. Uptake of antidepressants, antipsychotics, and antiepileptics remained as expected when stratified by gender, age, single-person household, deprivation, and urbanicity. Significant increases were observed in uptake of hypnotics in people younger than 18 years and older than 65 years, and in anxiolytics for people older than 65 years. Interpretation: Our results suggest stockpiling of medications in March, 2020, with lockdown associated with increased hypnotics in children, and hypnotics and anxiolytics in older people. There remains no evidence of restrictions impacting antidepressant or antipsychotic uptake. Funding: UK Research and Innovation Administrative Data Research Centre Northern Ireland (grant number ES/S00744X/1) and the Northern Ireland Public Health Agency Health and Social Care Research and Development (grant number COM/5625/20).